Exploring the Perspectives of Professionals on Providing Intimate Partner Violence Services to Women With Disabilities - Namatovu, Fredinah (Violence against women, 2024)
This study explored the experiences and perceptions of professional service providers offering services to women with disabilities exposed to intimate partner violence (IPV). Eighteen in-depth interviews were conducted with service providers working in health care, social work, the police, women’s shelters, and the Centre for Violence Against Women. Our findings suggest that providing adequate IPV services to women with disabilities requires coordination and collaboration. IPV services were organized around five overarching themes: finding services; assessing the risk; identification; protection and care; and becoming independent. This approach was helpful for women who faced disability-related challenges in accessing IPV services.